Proceedings of the 6th international conference on cartography & GIS, 13-17 June 2016, Albena, Bulgaria - Konecny, M. (Bulgarian Cartographic Association, 2020)
Material presents some problem: Ica’s modern cartography; cartographiy and its connecting role; Evaluating regional education systems performances in Spain and their influence in the socioeconomic system; Gis-based automated valuation models (avms) for land consolidation schemes demetris demetriou; Development of a Gis database for agro-ecological characterization of the razlog region (Southern Bulgaria); Advanced analysis tools and techniques in arcgis and smart mapping.